Dynamic Attendance System / Choe Kar Hooi - Choe, Kar Hooi (2003)
DAS, an abbreviation for Dynamic Attendance System, serve the purpose for Flexi Hour Working System. It is developed to replace the current attendance system, which is not computerized in Guan Seng Stationary Sdn. Bhd. By using this system, the attendance information of all the employees will be automatically recorded. This will reduce the job of administrator and also reduce the cost for paper. This will help to increase quality and accuracy in data keeping, yet provide up-to-date and economical way of information management. More important is this proposed system will provide safeguards to ensure reliability, accuracy and confidentiality of the information. DAS consists of several modules or sections. Staff module, which enable employees to view their record. Supervisor module, which enable the supervisor to get automatic report weekly and also they will be able to view the report they selected. Administrator module enable administrator to edit staffs' information; for example like adding new employees and also deleting employees. The proposed system will be develop by using Waterfall with Prototyping model. Tools that are chosen for the system development are Visual Basic .NET, Windows 2000, MS SQL Server 2000, HTML, Microsoft Photo editor, Microsoft Scheduler, and Internet Information Server. The Web-based DAS is a kind of office automation, which developed with the purpose to replace current paperwork used in Guan Seng Stationary Sdn. Bhd. This system is hope to reduce the data storage cost and increase the efficiency of data storage.